ANTIPSYCHOTIC ACTIVITY OF AQUEOUS ETHANOLIC EXTRACT OF TINOSPORA CORDIFOLIA IN AMPHETAMINE CHALLENGED MICE MODEL - Abhilasha Shete; Vibhor Kumar Jain; Bindu nee Giri Jain (Wolters Kluwer Medknow Publications, 2010)
Tinospora cordifolia is reported to have CNS active principle and is used for thetreatment of various neurological disorders. Hence, the effect of aqueous ethanolicextract of Tinospora cordifolia was investigated for its putative antipsychotic activityusing amphetamine challenged mice model. Haloperidol (1 mg/kg i.p.) was administeredacutely to mice as standard drug. Control animals received vehicle (10% DMSO). The invivo receptor binding studies were carried out to correlate the antipsychotic activity ofthe extract with its capacity to bind to the DAD2 receptor. The results in SLA showed thatthe hydro alcoholic extract of the stems of Tinospora cordifolia at a dose level of 250mg/kg and 500 mg/kg showed no significant antipsychotic activity in amphetamineinduced hyperactivity in mice when compared to standard. Extract alone treated group ata dos level of 250 mg/kg and 500 mg/kg showed a decreased in locomotor activity whencompared to the control. The plant extract increased the DAD2 receptor binding in a dosedependent manner in treated mice compared to the control group.